PERAN PENYULUH DALAM IMPLEMENTASI USAHATANI JERUK NIPIS BERKELANJUTAN DI DESA LANDONO DUA KECAMATAN LANDONO KABUPATEN KONAWE SELATAN - Sukani, Niluh Putu; Rianse, Usman; Abdullah, Sukmawati (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
The objective of this study is to ascertain the role of extension agents in the implementation of sustainable lime farming practices in Landono Dua Village, Landono District, South Konawe Regency. The population under investigation in this study consisted of lime farmers in Landono Dua Village, Landono District. The study sample was obtained through a census, resulting in a total of 49 individuals. This research employs a quantitative methodology. The variables under investigation are divided into two categories: the role of extension workers and the sustainability of lime farming. The data were collected through observation, interviews, and document analysis using questionnaires as the primary data collection instrument. The data were processed using a quantitative descriptive method, employing the class interval formula. The findings revealed that the role of agricultural extension agents can be classified into five distinct roles: facilitator, innovator, motivator, dynamizer, and educator. The role of agricultural extension workers in this study is categorized as positive, as evidenced by the effective implementation of the five roles identified. The sustainability of farming is divided into five aspects: ecological, economic, and social. The implementation of lime farming sustainability in this study is categorized as positive, indicating that the three aspects of sustainability have been applied effectively and have yielded positive results.